2022
DOI: 10.4018/ijsi.289166
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of Technology on Digital Economy Development in Vietnam

Abstract: The increases in ICT infrastructure/equipment investment and increased ICT adoption tend to be strongly correlated with economic growth and productivity, However, the digital economy needs more participation of digital government and the people who run the economy play an important role. Economy operators/leader need to be equipped with a sufficiently deep understanding of technology trends and innovation technology to apply digital economy development. Digital technology has significantly changed the speed of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The impact of access quality on developing countries is more obvious. Tan et al ( 2021 ), by comparing the digital economy of Vietnam and other ASEAN countries, confirmed that ICT infrastructure and ICT such as the Internet are the driving factors of digital economy growth and emphasized the importance of digital government, active participation, and policy orientation.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of access quality on developing countries is more obvious. Tan et al ( 2021 ), by comparing the digital economy of Vietnam and other ASEAN countries, confirmed that ICT infrastructure and ICT such as the Internet are the driving factors of digital economy growth and emphasized the importance of digital government, active participation, and policy orientation.…”
Section: Discussionmentioning
confidence: 99%